Variation in maturity observed along individual cotton fibers using confocal microscopy and image analysis. Issue 8 (May 2015) - Turner, Chris; Sari-Sarraf, Hamed; Hequet, Eric; Vitha, Stanislav
A prior work describing a computer vision system for measuring maturity using longitudinal views of cotton fibers reported observing a large variation in maturity within a single fiber. This paper describes the use of confocal microscopy as an independent measuring method to validate those findings. Individual cotton fibers are imaged from end to end by a confocal microscope producing hundreds of image volumes of cotton fiber segments, each ∼150 µm in length. From these volumes, virtual fiber cross-sections are extracted, processed using the level set method, and measured according to AATCC standards. The results demonstrate with both visual and quantitative analysis that fiber maturity can exhibit large variations within a single fiber.